PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERORIENTASI PENDEKATAN SAINTIFIK PADA POKOK BAHASAN LARUTAN ASAM-BASA KELAS XI SMA - Sinta Marito. B; Susilawati '; Abdullah ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is a Research and Development (R & D). The development process has been done with reference to 4-D model with steps of Defenition, Design, Development, and Disseminate. Research was conducted in FKIP UR. This research aims to obtain a student worksheet oriented scientific approach on the subject of the acid-base solution for class XI SMA. The research and development with 4-D model was conducted only until Development step, because the purpose of this research was limited to develop and produce a valid student worksheet to be implemented based on validator assessment. Feasibility of student worksheet was evaluated from feasibility of content, language, presentation, graphical and scientific approach aspects. Student worksheet validation result obtained an average value as 4,53 which showed that student worksheet which developed was valid. Means, student worksheet oriented scientific approach on the subject of the acid-base solution for class XI SMA that was developed, suitable to be used in learning process.Keyword : Scientific Approach, Worksheet Students, and Acid-Base Solution